Variability in fruit morphology and germination capacity of the tropical medicinal species securidaca longipedunculata Fres. - Daboué, Edith M. S.; Béné, Ali; Dimobe, Kangbéni; Dayamba, Djibril S.; Zouré, Aboubacar B.; Ouattara, Bassiaka; Sabo, Prospère; Tuina, Sévérin; Neya, Oblé; Vinceti, Barbara; Ouédraogo, Amadé (MDPI, 2024)
Securidaca longipedunculata Fresen, a medicinal tree indigenous to tropical Africa, faces threats due to root overharvesting and limited occurrence. This study assessed the extent of variation in the morphological traits and germination of seeds collected from populations located across the Sudano-Sahelian and Sudanian climatic zones in Burkina Faso. A total of 1600 mature fruits across the two climatic zones were characterized in their morphology. Seed germination tests were conducted with material collected across climatic zones, using six physical and chemical pre-treatments and two substrates. Descriptive statistics and analyses of variance were used to process the data generated. The morphological data showed significant variations in fruit and nut traits across the populations sampled, which may reflect a significant underlying genetic diversity, as expected in wild plants. Samples from the Sudano-Sahelian zone exhibited larger fruits (11.87 ± 1.38 mm) containing heavier (0.12 ± 0.04 g) and larger (5.64 ± 1.02 mm) nuts. Seeds sown on river sand exhibited the highest mean germination percentage (35.24 ± 17.73%) and germination speed (0.40 ± 0.36 seedlings per day). Seed wing and coat removal resulted in the highest mean germination percentages (respectively, 36.5 ± 19% and 35.5 ± 16%). These results suggest the existence of some barriers to germination in S. longipedunculata seeds. For seedling production, preferably heavier fruits should be collected and sowing carried out on river sand after wing or coat removal.